Treatment of aggression behaviors in a child diagnosed with ASD support level 1: Case report (Research, Society and Development, 2024)
Assessing problem behaviors related to aggression might encompass a great risk to the patient themselves and therapists. The search for safe assessments and interventions, that subject the patient and the people involved to a lower risk for physical damage and trauma, has been an recurrent topic in scientific literature. This report aims to present data regarding the implementation of IISCA, functional communication, tolerance and cooperation training with a child diagnosed with Autism Spectrum Disorder (ASD), level 1, as well as to evidence the effectiveness of applying data found in applied research to service provision at a care center specialized in Applied Behavior Analysis for Autism and related disorders. The intervention proved to be effective, reducing target behaviors to level zero, or close to it, during intervention sessions and 3 and 6 months follow-up. Finally, the benefits of the procedures adopted and the need for more reports on transposition of interventions derived from applied research to service provision are discussed.